Innovation of Walker for People with Disabilities using Bamboo Waste and Kenaf Fibers Reinforced Composites - Harini Sosiati; Tri Wahyono; Ankas Pamasti; Arif Muhammad Rizky; Revlyn Himawan; Yashinta Farahsani; Sinin Hamdan (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
Bamboo has many benefits from roots to stems and is very easy to obtain in Indonesia. Bamboo is widely used for handicraft products, woven materials, textiles, buildings, and bridges. In addition, bamboo fiber has also been processed into various products to increase its potential and economic value, namely for applications in the field of engineering, including automotive, aircraft, and solar panels. However, the availability of bamboo fiber in Indonesia is not easy to obtain, and bamboo waste from handicraft products is generally only used for fuel. The bamboo waste is combined with natural kenaf fiber and processed into a composite material with an epoxy resin binder through this community service activity. The composite product is then used to innovate the walking aids (walkers) for people with disabilities, namely by adding eating and drinking mats to the walker. The composite material has also been tested for its impact toughness before use. This innovative product is expected to increase user benefits in rural communities.